Remote Medical Applications of Artificial Intelligence - Rini Kartika Hudiono; Sri Watini (Pandawan Sejahtera Indonesia, 2023)
Artificial intelligence, usually referred to as AI, is one of thetechnologies that is a cornerstone for the sustainability ofhuman activities. When we hear the term AI, we instantly seerobots that can perform tasks independently much like aperson. An artificial intelligence (AI) system might be used toforetell user interests. What role does artificial intelligence (AI) playin the usage of telemedicine, for instance, in the context of mobileapplications? Benefits for the patient will be provided through theapplication of AI technology. Definition of mobile telemedicine as itrelates to Halodoc refers to a network-based health consultationservice that allows patients and doctors to consult. AI may research apatient's history and the actions that are performed on them. In orderto increase performance efficiency between physicians and patientsand ensure the security and confidentiality of patient data, this datacollection generates suggestions regarding services and complaintswithout directly contacting the doctor, patient information privacy,etc.